Management of paediatric desmoid fibromatosis. (24th May 2012) - Holme, HK; Westbury, C; Morgenstern, D; Erturan, G; Tirabosco, R; Pollock, R; Briggs, T; Cassoni, A; Michelagnoii, M
Abstract : Aims: Review the experience of a single institution's multi-disciplinary sarcoma group with regards management of fibromatosis. Methods: Retrospective analysis of case notes of all young people (<21 years), with histological diagnosis of desmoid fibromatosis confirmed by expert pathology review, treated between 2003-2010. Results: Thirty-two records were analysed; 4 children seen as second opinion only were excluded. There were 22 girls and 6 boys (3.7:1 ratio). Median age at diagnosis was 13.9 years. Twenty-three out of 28 children underwent surgical resection; 4 had complete microscopic resection, despite which 3 relapsed at a median of 13 months. Of the remaining 19 children with intra-lesional/unknown disease clearance, 4 remain in continued radiological remission at a median of 50 months, 4 had residual disease on MRI, and 11 had progressive disease at median 10.5 months after surgery. Hormonal therapies and/or non-steroidal anti-inflammatory drugs were used for 12 children; 8 had stable disease at median 43 months, whilst 3 progressed at a median of 20 months and response assessment is awaited in 1. Three with stable disease had concomitant radiotherapy. Eleven children were treated with cytotoxic chemotherapy (11 episodes), with progression after 4 episodes at a median of 29 months from diagnosis, while post 6 episodes stable/responsive disease was achieved at a median 35 months. Response assessment in 1 child is awaited. Eleven children received radiotherapy, with 1 child receiving 2 separate courses (different anatomical sites). Three children had progressive disease following radiotherapy (including the child with multi-focal disease) at a median of 67 months, whilst the remaining 8 (72%) children achieved stable/responsive disease at a median of 51.5 months. Conclusions: With a caveat of small numbers, complete resection is technically more demanding and does not necessarily have a clear outcome advantage compared with incomplete histological resection. We propose excision should only be attempted if associated morbidity is low. Chemotherapeutic and non-cytotoxic agents are an alternative to avoid surgery and radiotherapy in the growing child. Radiotherapy was associated with induction of responsive/stable disease in 72% and is a useful therapy, although concerns about the impact on the growing child will limit its wider use in this patient group.